PENGARUH KUALITAS PELAYANAN DAN FASILITAS SEBAGAI PENENTU KEPUASAN WISATAWAN VALKA BALI HOTEL - I Putu Satwika; Putri Anggreni; Ni Luh Yuli Tresna Dewi (Nusantara Hasana Journal, 2023)
This research aims to determine the partial and simultaneous influence of service quality and facilities on Valka Hotel tourist satisfaction. The method used in this research is a quantitative descriptive method using a type of research with a survey method with a data collection instrument in the form of a questionnaire to obtain information about a number of respondents representing a certain population which will then be carried out statistical data analysis (SPSS) to test the hypothesis that has been proposed. . Valka Bali Hotel is a 3 star hotel established in 2016 which is located in the Seminyak area of ​​Bali, more specifically the road. Kunti 1, alley banana no. 1 Seminyak, Kuta subdistrict, Badung Regency, Bali Province, Valka Bali which is part of the CV. August 2016 Valka Bali started using a website system where this system can be accessed throughout the world, making it easier for guests to book rooms. The results of this research found that the quality of service and facilities had a partial and simultaneous effect on Valka Bali Hotel tourists. Where the multiple linear regression model research results are as follows Ŷ= 5.398+0.256X1+0.464X2. Which can be interpreted as follows, the constant value is 5.398, meaning that if the service and facility quality variable is equal to zero, then tourist satisfaction is 2.867. The beta coefficient value for the service quality variable is 0.253, which means that every change in the service quality variable (X1) of one unit will result in a change in tourist satisfaction (Y) of 0.010 units. with other assumptions being constant. Meanwhile, the beta coefficient value for the facility variable is 0.250, which means that every change in the facility variable (X2) of one unit will result in a change in tourist satisfaction (Y) of 0.004 units with other assumptions being constant.